Therapist Self-Efficacy in Delivering Cognitive Processing Therapy in a Randomized Controlled Implementation Trial. Issue 3 (August 2021) - Pace, Brian T.; Song, Jiyoung; Suvak, Michael K.; Shields, Norman; Monson, Candice M.; Stirman, Shannon Wiltsey
Highlights: Therapist self-efficacy improved as they delivered cognitive processing therapy. Therapists' clinical outcomes varied by consultation condition. Low self-efficacy therapists with consultation had better clinical outcomes. Therapist self-efficacy was unrelated to observer-rated treatment fidelity. Abstract: Efforts to improve the implementation of evidence-based treatments (EBT) have recently made important strides. One such example is understanding the vital role that weekly consultation plays as therapists learn to deliver an EBT. Because mechanism-based research can further support EBT implementation, the present study sought to examine the potential relationship between therapist self-efficacy in relation to treatment fidelity and outcomes. We examined therapist self-efficacy ratings from 80 therapists working with 188 patients. These data were collected as part of a randomized controlled implementation trial testing cognitive processing therapy (CPT). Across post-workshop training conditions, we ran multilevel models to assess (1) changes in therapist self-efficacy, (2) therapist self-efficacy in relation to treatment fidelity, and (3) therapist-self-efficacy in relation to patient PTSD symptom outcomes. We found that therapist self-efficacy significantly improved over the course of 6 months of CPT training. Baseline therapist self-efficacy was differentially associated with client outcomes based on post-workshop training condition. Specifically, therapists with low self-efficacy that did not receive post-workshop consultation tended to have poorer outcomes than therapists with low self-efficacy that received consultation. In the present sample, therapist self-efficacy was not related to treatment fidelity. As this was the first study to examine therapist self-efficacy in the implementation of an evidence-based treatment, our findings suggest that self-efficacy may be an important implementation factor in treatment outcomes and worthy of ongoing research.